Psikoterapi dan Tasawuf Dalam Mengatasi Krisis Manusia Modern - Elvira Purnamasari (IAIN Bengkulu, 2019)
This paper contains a spiritual crisis that is running rampant in modern times. Because modernization not only encourages economic progress, technology and science but also creates a spiritual crisis that makes life feel empty, and meaningless. The purpose of this paper is to understand what are the main problems that caused the spiritual crisis and how Islamic psychotherapy comes from the teachings of the Qur'an and the Traditions of the Holy Prophet. and a life of Sufism that continues to strive to draw closer to God Almighty can be a solution in overcoming the spiritual crisis suffered by modern humans today. Sufism with its zuhud attitude will eliminate the fetters of love of the world that undermine the human soul and Islamic psychotherapy will be able to fill the empty human heart and empty with spiritual values that have been lost from him.